Haemophagocytic lymphohistiocytosis in Adult- A Case Report and Literature Review - Hossain, Syeda Fahmida; Qureshi, Nazmul Kabir; Mahmud, Zahid; Hossain, Md Iqbal (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Haemophagocytic lymphohistiocytosis (HLH) is a rare but potentially fatal disease of normal but overactive histiocytes and lymphocytes that commonly appears in infancy, although it has been seen in all age groups. The disease may be inherited or acquired due to infections, collagen vascular diseases and malignancies. The pathological hallmark of the syndrome is uncontrolled activation of T lymphocytes and macrophages, together with an impaired cytotoxic function of NK cells and CD8+ T lymphocytes, resulting into massive cytokine release (e.g., interferon , TNF á, interleukin[IL]-6, 8,10,12,18 etc) from these cells and overwhelming inflammation. Lymphocytes and macrophages, sometimes with haemophagocytic activity accumulate in bone marrow, spleen, liver, or lymph nodes. This immune dysregulatory disorder is characterized by fever, hepatosplenomegaly, lymphadenopathy, skin rash, cytopenias, hepatitis, coagulopathy, neurological symptoms. We report a case of 65 years old male presenting with fever and erythroderma who developed typical clinical and laboratory findings consistent with diagnosis of HLH according to HLH-2004 guidelines. Despite receiving etoposide based chemotherapy, the patient succumbed rapidly from progressive HLH. This case high lightened the diagnostic challenge and the need for keeping a high index of suspicion for promptly diagnosis and treatment of this potentially life threatening condition as clinical features and laboratory investigations are non specific. J Bangladesh Coll Phys Surg 2015; 33(3): 166-176